Unsafe reasoning: a survey - Faria, Paulo (DoisPontos, 2009)
Judgments about the validity of at least some elementary inferential patterns (say modus ponens) are a priori if anything is. Yet a number of empirical conditions must in each case be satisfied in order for a particular inference to instantiate this or that inferential pattern. We may on occasion be entitled to presuppose that such conditions are satisfied (and the entitlement may even be a priori), yet only experience could tell us that such was indeed the case. Current discussion about a perceived incompatibility between content externalism and first-person authority exemplifies how damaging the neglect of such empirical presuppositions of correct reasoning can be. An externalistic view of mental content is ostensibly incompatible with the assumption that a rational subject should be able to avoid inconsistency no matter what the state of her empirical knowledge may be. That fact, however, needs not be taken (as it often is) as a reductio of externalism: alternatively, we may reject that assumption, adding to the agenda of a philosophical investigation of rationality an examination of the vicissitudes of logical luck. I offer an illustration and defense of that alternative.
n/a
Keywords: Content externalism; Exteriorismo de conteúdo; Inference; Inferência; Logical luck; Pressuposição; Presupposition; Sorte lógica